Electrophysiological Characterization of Spontaneously Contracting Cell Aggregates Obtained from Rainbow Trout Larvae with Multielectrode Arrays - Julia M. Mehnert; Matthias Brandenburger; Bianka Grunow (Cellular Physiology and Biochemistry, 2013)
Background/Aims: Safety pharmacology requires novel model systems for the detection of cardiac side effects. Ranging from cell-based systems to model organisms, no model available to date reflects the complexity of the human heart and evokes the great need for improved and more affordable systems. Many drugs interact with hERG potassium channels and consequently cause life threatening ventricular arrhythmias, further highlighting the importance of suitable model systems. Methods: Spontaneously Contracting Cell aggregates (SCC) as a 3D in vitro heart-syncytium obtained from rainbow trout larvae represent a novel model system for cardiac safety pharmacology. SCCs can be harvested cost-effectively and kept in culture for several weeks while retaining their functionality and displaying contraction rates similar to the human heart. Results: Extracellular field potential recordings with multielectrode arrays revealed significant prolongation of field potential duration upon administration of common hERG potassium channel blockers. Infusion of 1 µM Dofetilide and 10 µM Terfenadine prolonged field potentials 10 fold and 2 fold, respectively. In addition, SCCs enabled analysis of autonomous contraction frequencies. Conclusion: Thus, SCCs represent a novel and low-cost cardiac model system of the human heart for application in safety pharmacology.